GRP-041 Collection and Analysis of Adverse Effects and Co-Medications For Outpatients Receiving Boceprevir- or Telaprevir-Based Treatment For Chronic Hepatitis C. (12th March 2013) - Carré, N; Lemaître, G; Abbas, N; Guérin, C
Abstract : Background: The current treatment of chronic genotype 1 hepatitis C virus infection is the triple combination of peginterferon, ribavirin and a new direct-acting antiviral (DAA), either telaprevir (TVR) or boceprevir (BOC). Potential adverse drug reactions (ADRs) represent an important problem in patient safety. In addition, the DAAs increase the risk of drug-drug interactions (DDIs). Purpose: Guided pharmaceutical interviews were conducted (i) to invite patients to provide feedback on the ADRs, to follow known DDIs, (ii) to encourage patients to communicate potential problems and to adapt pharmaceutical advice. Materials and Methods: The study was conducted between January and April 2012. Patient interviews on ADRs and DDIs were performed every month, during drug dispensing for outpatients by hospital pharmacists. They collected data based on questionnaires which included the documented adverse effects [1, 2] and co-medications [3]. Results: 56 questionnaires were completed with TVR patients and 65 with BOC patients. A total of 41 TVR and 62 BOC patients were examined for ADRs (data from the first month were excluded). All patients had ADRs like those reported in the SPC (1, 2). The most common ADRs were anaemia (52%) and cutaneous manifestations (65%), especially dry skin (44%). Anaemia was more frequent in patients on BOC (56% BOC/45% TVR) but could be more severe with TVR: 55% of BOC patients and 29% of TVR patients were given erythropoietin and no BOC, but 3 TVR patients were transfused. Fatigue, rash, and pruritus were more frequent with TVR patients. Some ADRs were reported only by BOC patients: dysgeusia, alopecia and weight and appetite loss. Since DAAs are CYP 3A4 substrates and inhibitors, 58 potential interactions were identified and sometimes required close monitoring. Conclusions: Interviews enabled patients to talk about their ADRs and to express feelings on difficulties faced during their treatment. Hospital pharmacists gave them, in response, moral support and modified the advice they gave. They put patients' mind at rest about ADRs and raised patients' awareness of potential DDIs. Finally, the results on ADRs were reported to the health authorities in order to contribute to monitoring the risks related to these new drugs. References Summary of product characteristics (SPC) of telaprevir (Incivo). Available on the European Medicines Agency website: http://www .ema.europa.eu Summary of product characteristics (SPC) of boceprevir (Victrelis). Available on the European Medicines Agency website: http://www .ema.europa.eu The hepatitis drug interactions website available at: http://www .hep-druginteractions.org No conflict of interest.